We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
240
2
avatar

(ax-7)(bx+5) = 6x2+cx-35    If ab=6 and a-b=-1 what are two possible values of c?

 

I don't know if I'm on the right track, but so far I've found out that c=5a-7b

Please solve this problem for me and show me how you did it! Thanks :)

 

a) c=2 or c=-4

b) c=11 or c=-11

c) c=-2 or c=4

d) c=12 or c=-5

 Feb 14, 2018
 #1
avatar+557 
+1

a=2

b=3

(2x-7)(3x+5) substitute

6x²+10x-21x-35 expand

6x²-11x-35 rearrange

c=-11

or

c=11

choose option b)

 

 

winkwinkwink

 Feb 14, 2018
edited by lynx7  Feb 14, 2018
edited by lynx7  Feb 14, 2018
edited by lynx7  Feb 14, 2018
 #2
avatar+101360 
+2

(ax-7)(bx+5) = 6x^2+cx-35    If ab = 6 and a - b =  -1 what are two possible values of c?

 

(ab x^2  - 7bx + 5ax  -  35)  =  6x^2 + cx  -35

 

6x^2  + ( 5a - 7b) x - 35   =   6x^2  +  cx  -  35

 

5a  - 7b   =  c

 

If   a  - b  = - 1      then     b  =  a + 1

 

And

 

ab  = 6   ⇒   b   =  6/a

 

So

 

b   =   b

 

a  + 1   =  6/a           multiply through by a    and rearrange

 

a^2  + a  -  6   =  0   factor

 

(a - 2)  ( a + 3)  =  0      

 

Set each factor to 0  and solve and we get that   a  = 2  , a  = -3

 

When a  =  2      b  =  6 / a   =  3

When  a  = - 3     b  =  6/-3  =  -2

 

So

 

(a, b )  =   (2, 3)   or  ( -3, -2)

 

Using   5a  - 7b  = c

 

5(2)  - 7(3)  =  c  =  - 11

5(-3) - 7(-2)  = c  =  -1

 

Proof

a = 2  b = 3

( 2x - 7) ( 3x +  5)  =  6x^2  - 21x + 10x - 35   = 6x^2 - 11x - 35   ⇒   c  =  11

a = - 3, b = -2

(-3x - 7) (-2x + 5)  =   6x^2  - 15x + 14x - 25 = 6x^2 - 1x - 35       ⇒  c  = -1

 

 

cool cool cool

 Feb 14, 2018

15 Online Users

avatar
avatar
avatar
avatar